A Study of Customer Expectation Resulted from Merger and Acquisition Between Tot and Cat Telecom Company Limited - Putthiwanit, Chutinon; Suriyakul Na Ayudhya, Pattama (Journal of Roi Kaensarn Academi, 2024)
This research aims to find the effect of merger and acquisition (M&A) on customer expectation and satisfaction. Authors drew the case of TOT Company Limited merging with CAT Telecom Company Limited On 7th January 2021, resulting in a new brand name of ’National Telecommunication Company Limited (NT)’ with a combined total asset of three hundred billion baht. Even though TOT and CAT were major telecommunication service providers in Thailand, they function differently. Such M&A can affect many stakeholders. Therefore, the authors would like to fill in this discrepancy paradigmatically and wishfully solve such problems. Structural Equation Modelling (SEM) was used to find the influence and relationship of variables quantitatively, and the sample of 565 respondents (drew from Thai population) answered the questionnaire. Moreover, it was concluded that M&A Features affect customer expectations. While customer expectations mediated by M&A features have a positive impact on customer satisfaction. Customer expectations also positively affect customer satisfaction. And finally, M&A features positively and directly affect customer satisfaction. For future research, it is also of interesting that whether the organizational culture of the bigger firm in M&A, after M&A, will influence the smaller firms or not.